Structural and Functional Implications of the Interaction between Macrolide Antibiotics and Bile Acids. Issue 11 (5th February 2015) - Glanzer, Simon; Pulido, Sergio A.; Tutz, Sarah; Wagner, Gabriel E.; Kriechbaum, Manfred; Gubensäk, Nina; Trifunovic, Jovana; Dorn, Markus; Fabian, Walter M. F.; Novak, Predrag; Reidl, Joachim; Zangger, Klaus
Abstract Macrolide antibiotics, such as azithromycin and erythromycin, are in widespread use for the treatment of bacterial infections. Macrolides are taken up and excreted mainly by bile. Additionally, they have been implicated in biliary system diseases and to modify the excretion of other drugs through bile. Despite mounting evidence for the interplay between macrolide antibiotics and bile acids, the molecular details of this interaction remain unknown. Herein, we show by NMR measurements that macrolides directly bind to bile acid micelles. The topology of this interaction has been determined by solvent paramagnetic relaxation enhancements (solvent PREs). The macrolides were found to be bound close to the surface of the micelle. Increasing hydrophobicity of both the macrolide and the bile acid strengthen this interaction. Both bile acid and macrolide molecules show similar solvent PREs across their whole structures, indicating that there are no preferred orientations of them in the bile micelle aggregates. The binding to bile aggregates does not impede macrolide antibiotics from targeting bacteria. In fact, the toxicity of azithromycin towards enterotoxic E. coli (ETEC) is even slightly increased in the presence of bile, as was shown by effective concentration (EC50) values.